2005
DOI: 10.1515/jpm.2005.058
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and vaginal repair of uterine scar dehiscence following cesarean section as detected by ultrasound

Abstract: Patients with a history of CS should undergo transvaginal sonography of the scar region in order to detect latent scar dehiscence in combination with uterine wall thinning prior to planning further pregnancy. In suspected cases, a combined laparoscopic - vaginal or vaginal approach can be employed to repair the defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 41 publications
1
58
1
3
Order By: Relevance
“…Several case reports, case series and small prospective cohort studies with a maximum of 38 included women and one larger retrospective comparative study ( n  = 59) have been reported 5, 12, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35. Eleven articles (including a total of 65 women) reported a reduction or complete resolution of postmenstrual spotting; however, this was mostly not measured in a standardised way 5, 16, 18, 20, 21, 24, 26, 27, 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports, case series and small prospective cohort studies with a maximum of 38 included women and one larger retrospective comparative study ( n  = 59) have been reported 5, 12, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35. Eleven articles (including a total of 65 women) reported a reduction or complete resolution of postmenstrual spotting; however, this was mostly not measured in a standardised way 5, 16, 18, 20, 21, 24, 26, 27, 29.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven articles (including a total of 65 women) reported a reduction or complete resolution of postmenstrual spotting; however, this was mostly not measured in a standardised way 5, 16, 18, 20, 21, 24, 26, 27, 29. Pelvic pain and/or dysmenorrhoea was reported to be resolved after laparoscopic niche resection in 36 women 5, 18, 21, 29. The residual myometrial thickness was increased after laparoscopic niche resection in all studies, but only three studies compared the outcomes with baseline measurements 15, 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…Klemm and colleagues suggested that transvaginal sonography could be performed under laparoscopic vision if the scar piercing can not be immediately seen after cutting the bladder peritoneum and dissection of the uterovascular layer [9]. In our case, we used uterine manipulator porcelain to distinguish the bladder border.…”
Section: Discussionmentioning
confidence: 95%
“…These include conditions such as scar pregnancy, placenta accreta, placenta previa, and uterine rupture in subsequent pregnancies [2,3]. The CSD is also associated with abnormal bleeding, dysmenorrhea, pelvic pain, adenomyosis, infertility, abscess formation, post-coital bleeding during the non-pregnant state [4][5][6]. Of note, the most common clinical symptom is abnormal bleeding, and the correlation with CSDs has been well established.…”
Section: Short Communicationmentioning
confidence: 99%